2017
DOI: 10.2147/oajsm.s106699
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament injury/reinjury in alpine ski racing: a narrative review

Abstract: The purpose of the present review was to: 1) provide an overview of the current understanding on the epidemiology, etiology, risk factors, and prevention methods for anterior cruciate ligament (ACL) injury in alpine ski racing; and 2) provide an overview of what is known pertaining to ACL reinjury and return to sport after ACL injury in alpine ski racing. Given that most of the scientific studies on ACL injuries in alpine ski racing have been descriptive, and that very few studies contributed higher level scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 88 publications
(309 reference statements)
0
49
0
2
Order By: Relevance
“…In alpine ski racing, increased knee valgus loading often leads to neurophysiological injuries (Spörri et al, 2017 ). Three mechanisms were identified for ACL injuries, among which the dynamic snowplow and the slip catch can be partly attributed to increased knee valgus loading (Bere et al, 2011 ; Jordan et al, 2017 ). In the present study, only one male athlete sustained an ACL injury; however, the knee was the most affected body part by traumatic and overuse injuries, and ligament injuries in the knee frequently occurred.…”
Section: Discussionmentioning
confidence: 99%
“…In alpine ski racing, increased knee valgus loading often leads to neurophysiological injuries (Spörri et al, 2017 ). Three mechanisms were identified for ACL injuries, among which the dynamic snowplow and the slip catch can be partly attributed to increased knee valgus loading (Bere et al, 2011 ; Jordan et al, 2017 ). In the present study, only one male athlete sustained an ACL injury; however, the knee was the most affected body part by traumatic and overuse injuries, and ligament injuries in the knee frequently occurred.…”
Section: Discussionmentioning
confidence: 99%
“…In [7,8], Jordan et al made a review in which they report literature finding that only 55% of alpine skiing athletes are able to return to their preinjury level after an ACL rupture. They also support the result we have found that in this group of skiers there is no sex difference in ACL injury rates.…”
Section: Athlete Skiersmentioning
confidence: 99%
“…In [12], and also in two interesting reviews [7,21], proposed injury mechanisms are explained; a summary of this is of high interest for a better understanding of knee injuries in skiers:…”
Section: Acl Biomechanics and Injury Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations